Recycled culture in contemporary art and culture : the uses of nostalgia - Dika, Vera (C. U. P, 2003)
The reuse of images, plots and genres from film history has become prominent in contemporary culture. In this study, Vera Dika explores this phenomenon from a broad range of critical perspectives, examining works of art and film that resist the pull of the past. Dika provides an in-depth analysis of works in several media, including performance, photography, Punk film, and examples from mainstream American and European cinema. Proclaiming the renewed importance of the image and of genre, she investigates works as diverse as Cindy Sherman's Untitled Film Stills, Amos Poe's The Foreigner, Terence Malick's Badlands, and Francis Ford Coppola's One from the Heart. Her study positions avant-garde art work within the context of contemporary mainstream film practice, as well as in relationship to their historical moment.